Lordship, State Formation and Local Authority in Late Medieval and Early Modern England - Gibbs, Spike (Cambridge University Press, 2025)
Drawing on untapped archival records, this book provides new insights into lord-tenant relations, state formation, social inequality, political participation and everyday life in rural societies. This title is part of the Flip it Open Programme and may also be available Open Access. Check our website Cambridge Core for details.